Diagnosis to perfect the special strength in water of Pinar del Río water polo players - Madelaine Ramos Rojas; Mercedes Miló Dubé; Santa Caridad González Corrales (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The present work had the objective of characterizing the current situation of the Man water polo school team athletes of the EIDE (School of Sport base formation) of Pinar del Río, in relation to the special strength in water, in order to give an answer to one of the technological demands that affects the performance in this sport. By means of empirical methods such as observation, it was found that the athletes, after the second half of the game, could not keep the same performance as in the first two, and a great physical wear was noticed in them, which responds to the lack of special strength in water to support the endurance to the aquatic environment and the struggle with the opponent. Surveys were applied to the coaches, which reflected that there are deficiencies in the planning of the training sessions, affecting the optimal preparation of the special strength in water. The review of the Integral Program of Preparation of the athlete (2016) was carried out, not finding specific methodological actions for the work of the special strength in water as a guide for the work of the trainers in the process of training of this capacity, other documents that are used by the trainers were also reviewed. Measurements were made to determine the level of special strength in water of these school athletes. The use of theoretical methods such as historical-logical, inductive-deductive, analysis-synthesis, and statistical-mathematical methods, specifically descriptive statistics, were also part of this study.